Analysis of Factors Affecting Rice Production and Its Associated Risks - Purnomo, Sodik Dwi; Sundari, Sri; Jati, Damar; Cahyo, Heru; Uripi, Cahyaningtyas Ria; Octisari, Sully Kemala; Luhita, Tiladela (Jurnal AGRISEP, 2025)
Effective risk management is essential for rice farmers to achieve sustainable agriculture. Rice production is inherently influenced by uncertainties that can lead to yield declines or, in severe cases, complete crop failure. These uncertainties arise from various factors, including climate change, nutrient leaching, soil erosion, landslides, floods, pests, and droughts. Such risks not only threaten production but also have short-term impacts on food security at regional and national levels, potentially resulting in rice scarcity and rising prices. This study aims to analyze rice production and its associated risks in Purbalingga Regency, Central Java. Using multiple linear regression and multiplicative heteroscedasticity regression methods, the study incorporates novel elements such as agricultural inputs (land size, seeds, urea fertilizer, pesticides, and machinery), socio-demographic factors (planting season, education, farming experience), and government policies (ownership of farmer cards and extension service intensity). The findings indicate that land area, urea fertilizer, pesticides, agricultural tools, Farmer Card ownership, extension services, and planting seasons significantly affect rice production and its risks. These results underscore the importance of enhancing farmers' capabilities through improved agricultural inputs, education, and a deeper understanding of evolving planting processes, ultimately enabling more effective risk management strategies.